Predictive and Contemporaneous Power of the Determinants of Stock Liquidity - Xie, Linyin; Jin, Yuanqing; Mo, Chanxuan (Frontiers in Psychology, 2022)
This study constructs nine (five) idiosyncratic (systematic) variables to test the predictive and contemporaneous power of the determinants of stock liquidity. We select A shares from January 2003 to September 2021 to study stock liquidity in the Chinese market. As a novel discovery, this study finds that stock liquidity abnormally decreases with contemporaneous idiosyncratic return and also with 1-year lagged systematic return. Only the idiosyncratic return variance can decrease future short-term or contemporaneous stock liquidity. Idiosyncratic factors are more important than systematic ones for contemporaneous and future stock liquidity. The predictive power of the determinants decreases with the forecast length. Economic policy uncertainty (EPU) can affect sensitivity of stock liquidity to contemporaneous determinants. The empirical results of this research are robust over subperiods, forecast length and across four liquidity measurements. The abnormalities and linkages between determinants and stock liquidity are correlated with investor psychology and special market mechanism in China.